2019
DOI: 10.1371/journal.pone.0225928
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Parkinson’s disease model rats exhibit hyperalgesia to subcutaneous formalin administration into the vibrissa pad

Abstract: We bilaterally injected 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle of rats and developed bilateral Parkinson’s disease (PD) model rats in order to experimentally investigate the neural mechanisms underlying the alteration of nociception in the orofacial region of patients with PD. We explored the effects of dopamine depletion on nociception by investigating behavioral responses (face rubbing) triggered by subcutaneous administration of formalin into the vibrissa pad. We also assessed the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The mechanisms underlying this hyperalgesia were examined by measuring the c-Fos expression in brain regions related to the DPIS, and the findings showed no differences in the number of c-Fos-IR cells in the vlPAG, LC, and NRM between 6-OHDA-lesioned and sham-operated rats receiving formalin injections. However, in the formalin injection group, 6-OHDA-lesioned rats exhibited a significant decrease in the number of c-Fos-IR cells in the ipsilateral PVN when compared to the sham-operated rats, and this finding was also in agreement with previous studies [19, 21]. Further examination showed that the number of c-Fos-IR cells in the ipsilateral mPVN and dpPVN of 6-OHDA-lesioned rats did not significantly differ by injection status (i.e., formalin injection vs no injection groups).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mechanisms underlying this hyperalgesia were examined by measuring the c-Fos expression in brain regions related to the DPIS, and the findings showed no differences in the number of c-Fos-IR cells in the vlPAG, LC, and NRM between 6-OHDA-lesioned and sham-operated rats receiving formalin injections. However, in the formalin injection group, 6-OHDA-lesioned rats exhibited a significant decrease in the number of c-Fos-IR cells in the ipsilateral PVN when compared to the sham-operated rats, and this finding was also in agreement with previous studies [19, 21]. Further examination showed that the number of c-Fos-IR cells in the ipsilateral mPVN and dpPVN of 6-OHDA-lesioned rats did not significantly differ by injection status (i.e., formalin injection vs no injection groups).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies investigating the cause of hyperalgesia in PD model rats have largely focused on the DPIS [3, 23, 24]. One study demonstrated a significant bilateral decrease in c-Fos-immunoreactive (-IR) cells in the PVN of PD model rats after SC injection of formalin into the vibrissa pad [19], while another observed similar results unilaterally in the hind paws of PD model rats [21]. The current study aimed to elucidate the mechanism underlying hyperalgesia in PD by examining DPIS neuronal nuclei activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty minutes prior to surgery, ION-CCI rats received an i.p. injection of desipramine hydrochloride (20 mg/kg, Sigma, St. Louis, MO, USA) to protect noradrenergic neurons and fibers [48,49]. ION-CCI rats then were anesthetized by i.p.…”
Section: Administration Of 6-ohda and Measurement Of Head-withdrawal Thresholdmentioning
confidence: 99%
“…administration of saline solution mixed with 2.0 mg/kg midazolam, 2.5 mg/kg butorphanol, and 0.375 mg/kg medetomidine and placed in a stereotaxic apparatus (Narishige, Tokyo, Japan) with the incisor bar set 3.3 mm below the level of the ear bars. Next, 2 mg of 6-OHDA (Sigma, St. Louis, MO, USA) in 1 mL of sterile saline containing 0.01% ascorbic acid was injected into the left A11 nucleus [15,48,49]. Stereotaxic coordinates for the 6-OHDA injection site were 3.9 mm caudal to the bregma, 0.5 mm left of the midline, and 7 mm ventral to the dural surface.…”
Section: Administration Of 6-ohda and Measurement Of Head-withdrawal Thresholdmentioning
confidence: 99%